Professional embedded ARM development - Langbridge, James A. (Wrox, a Wiley brand, 2014)
With more than 90 percent of mobile phones sold in recent years using ARM-based processors, developers are eager to master this embedded technology. If you know the basics of C programming, this guide will ease you into the world of embedded ARM technology. With clear explanations of the systems common to all ARM processors and step-by-step instructions for creating an embedded application, it prepares you for this popular specialty.